PENGARUH SISTEM PENGENDALIAN INTERN PENJUALAN TERHADAP EFEKTIVITAS PENJUALAN: STUDI KASUS PT. INTI (PERSERO) BANDUNG - Andhika Ariadharma (Fakultas Bisnis UKDW, 2017)
Sales is a major activity in companies that need to be taken seriously, because with the sale of thecompany to earn a profit for the company's survival. Given the importance of sales activity within thecompany, it is necessary to control the sale as well. Sales activity should be planned and carried outeffectively and efficiently as possible in order to profit the company can achieve the optimum point,and the company can also handle and control the sales activity well in line with the growing companyand competition in the business world. In this study, the researchers conducted a case study usingdescriptive analysis research methodology of data collection is done by questionnaires, interviews,observation, and research literature. The method used to test the hypothesis is a statistical method ofSpearman Rank correlation. Based on the results of questionnaires and hypothesis testing is done, theresults obtained by calculating the percentage of 69.22% so it can be concluded that the InternalControl System Sales is designed PT INTI (Persero) is very influence on sales effectivitness.Keywords: Internal Control System Sales, Sales Effectivitness